Контенсивне мапування ‘ECONOMY’ в англійській мові - Михайленко, Валерій Васильович; Mykhaylenko, V. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Концептулізація ‘ECONOMY’ в англомовній картині світу потрібна для моделювання змісту концепту та семантичної струк¬тури значення його домінантної лексеми. Використання концептуального, етимологічного та компонентного/ дефігіційного типів аналізу й верифікація їхніх результатів у рамках дискурсу на матеріалі Британського націо¬нального корпусу англійської мови дало можливість виокремити концептосферу ‘ECONOMY’, компонентну структуру домінантної лексеми та вирізнити її дискурсивні функції. The objective of the paper is to define the componential structure of the dominant lexeme and reveal its discourse functions. Conceptualizing ‘ECONOMY’ in the Anglo-phone world view is necessitated by modeling the concept content and the semantic structure of the lexeme in the English language system. Employing conceptual, etymological and componential/definitional types of analysis (dictionary entries) and their results verification in discourse registered in The British National Corpuse made possible to reveal the ‘ECONOMY’ conceptual system to show the ways of its semanticising in registered in the language system as well as in the discourse structure. The paper presented is a response to the challenges put forward by lexical and cognitive semantics, practical lexicography and teaching LSP ‘ECONOMICS’ to the ‘economics’ majors.
‘ECONOMY’ Сontensive Mapping in English
Keywords: концепт; concept; лексема; lexeme; компонент; component